THE ROLE OF MULTIMEDIA TECHNOLOGY IN THE EFFICIENEY OF PRESCHOOL - Boltaxo'jayeva Shabnambonu Sobir qizi (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the effectiveness of information technology and multimedia products in preschool education. The effectiveness of the multimedia platform created as a result of the implementation of preschool education. Information on it's practical use and effectiveness is provided.